Four weeks of meditation training improves sustained attention in community-dwelling older adults: a proof-of-concept randomized controlled trial - Ford, Sabrina D.; Nagamatsu, Lindsay S. (Frontiers in Aging, 2024)
INTRODUCTION: With our rapidly expanding population of older adults, identifying effective intervention strategies to improve cognitive functioning is an increasing priority. This study sought to examine whether four weeks of thrice-weekly meditation training can improve attention in older adults, as well as whether such benefits may extend to other domains of cognition as well as mobility. METHODS: Forty-three participants (mean age 68 years) were randomized into either the focused attention meditation group or the music listening control group (Clinicaltrials.gov ID NCT03417635). Participants completed three 20-minute guided group sessions per week for four consecutive weeks. Our primary outcome measure was behavioural performance on the Sustained Attention to Response Task (SART). Secondary and tertiary outcome measures included event-related potentials (ERPs) during the SART task, measures of executive functioning, and measures of mobility. RESULTS: We found that meditation training significantly improved attention, as demonstrated by improved SART accuracy and changes in N2 ERP amplitude and latency. DISCUSSION: These findings suggest that meditation may lead to changes in attention and underlying cognitive processing in older adults, although a full-scale definitive trial is needed. Future research on the long-term benefits with real world applications is warranted.